Neither “True Being” nor “Cosmic Pyrotechnics”: Dewey’s Naturalistic Metaphysics as Environmental Pedagogy Aid - Warren, Sarah (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
Drawing primarily on John Dewey’s Experience and Nature, but putting his metaphysical commitments into conversation with pedagogical experience, this article asks: how might a Deweyan understanding of nature and our experience within it support environmental progress? More specifically, how might we respect pluralistic relationships with philosophy in the classroom while simultaneously cultivating an understanding of experience that clarifies the embodied nature of our meaning-making within it and the contextual urgencies of today? How might observing the “generic traits of existence” and their particular and qualitative manifestations foster an appreciation for how the natural world acts as wellspring of human values? For Dewey as well as William James, experience is “double barreled,” designating both the “planted field” and “the one who plants and reaps”: functional distinctions serve a purpose, but experience emerges at, and astride the tensional energies that characterize, the permeable boundaries of self and world. Taking Dewey’s insights to heart illuminates how issues like biodiversity preservation are deeply existential concerns that are ripe for a Deweyan pedagogical intervention.